Upper Airway Findings and Markers of Lung Disease Progression in Patients with Cystic Fibrosis - Steffen,Luciane Mazzini (2020)
Abstract Introduction Cystic fibrosis (CF) is a genetic disease that limits the quality of life mainly due to respiratory symptoms. The relationship between findings of the upper airways and CF lung disease is not yet completely understood. Objective The aim of the present study is to describe the most frequent nasal findings and pathogens in patients with CF and investigate the association between the findings of the upper respiratory tract and markers of lung disease progression. Methods Retrospective study in patients with CF from the Pediatric Pulmonology Department who underwent otorhinolaryngological evaluation between 2015 and 2017. Nasal endoscopy and nasal swab collection were part of the evaluation. The severity markers used were: percentage of predicted forced expiratory volume in the first second (FEV1%), body mass index (BMI) and the Shwachman-Kulczycki (SK) clinical score. Results A total of 48 patients with CF were included. The mean of the predicted percentage of FEV1% was 83.36 ± 30.04. The average 14 and SK score 89.11 ± 10.50. The bacteriology of the nasal swab was positive in 27 (54.1%) patients. Staphylococcus aureus was positive in 18 patients, Pseudomonas aeruginosa in 5, Pseudomonas cepacea in 3 and Stenotrophomonas maltophila in 1 patient. Nasal polyps were found in nine participants. Nasal polyps were found in nine participants and were associated with lower SK score. Conclusion The pathogens found in the upper airway were, in order: S. aureus, P. aeruginosa, P. cepacea e S. maltophila. The presence of polyps in the nasal cavity showed statistical significance and appears to have association with the prognostic factor measured by the SK score.